1978
DOI: 10.1073/pnas.75.3.1349
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the nervous system: Role of ontogenetic mechanisms in the evolution of matching populations

Abstract: Systems that depend for their function on the interacting expression of many genes will constrain evolution, because the effects of a heritable change will have to mesh with the effects of the unchanged genes in order to be functional. In general, it would seem that the more a system is built upon complex interactions (i.e., interactions requiring the cooperation of products of different genes), the fewer heritable changes will prove to be evolutionary. The nervous system is highly interdependent, and yet it h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(26 citation statements)
references
References 15 publications
3
23
0
Order By: Relevance
“…Any structural and biochemical anomaly that occurs early in development may mask its consequences on behavior with a combination of homeostatic mechanisms and developmental reorganization-the developmental buffers (Katz and Lasek, 1978;Lipp, 1979Lipp, , 1988Lipp and Schwegler, 1982;Katz, 1983). These may prevent the expression of many early thyroxine effects, or make them, at least, highly unpredictable.…”
Section: Discussionmentioning
confidence: 99%
“…Any structural and biochemical anomaly that occurs early in development may mask its consequences on behavior with a combination of homeostatic mechanisms and developmental reorganization-the developmental buffers (Katz and Lasek, 1978;Lipp, 1979Lipp, , 1988Lipp and Schwegler, 1982;Katz, 1983). These may prevent the expression of many early thyroxine effects, or make them, at least, highly unpredictable.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that trophic interactions might present important phylogenetic strategies [Katz and Lasek, 1978;Ebbesson, 1984;Black, 1986;Finlay et al, 1987;Purves, 1988;Williams and Herrup, 1988], but the molecular mechanisms have remained largely obscure. In the last two decades a significant amount of new data on ontogenetic roles of transcription factors as well as neurotrophins has emerged.…”
Section: Scope Of This Reviewmentioning
confidence: 99%
“…Traditionally, most apoptotic death was thought to occur in post-proliferative cells that have begun to form synaptic connections (Katz & Lasek, 1978;Oppenheim, 1985;Yaginuma et al, 1996;Clarke et al, 1998;Bennet et al, 2002;Buss et al, 2006). However, several studies have suggested that apoptosis may occur also in proliferating precursors (e.g., Nikolapopoulou et al, 2006).…”
Section: Introductionmentioning
confidence: 99%